Systematic theology. processions and persons - Sonderegger, Katherine (Fortress Press, 2020)
Katherine Sonderegger follows her monumental volume on the doctrine of God with this second entry of her Systematic Theology, which explores the doctrine of the Holy Trinity. Locating her analysis first in the Hebrew Scriptures, Sonderegger examines the thrice-holy God that is proclaimed to Isaiah in the sanctuary and manifested in the sacrifice of the temple. The book of Leviticus, read in conversation with Exodus, unfolds the doctrine of the Trinity under the character of holiness. In the one God, Trinity speaks of the life, movement, and self-offering of God, who is the eternal procession of goodness and light. In Israel's sacrificial covenant, the triune God is perfect self-offering: the eternal descent of the Father of Lights is the offering who is Son, eternally received and hallowed in the one who is Spirit. Anchoring the theology of the Trinity in Israel's Scriptures in this way elevates the processions over the persons, exploring the mystery of the Divine Life as holy, rational, and good. The Divine Persons, named in the New Testament, cannot be defined but may be glimpsed in the notion of perfection, a complete and perfect infinite set. In all these ways, the Holy Trinity may be praised as the deep reality of the life of God.